Eragon - Paolini, Christopher (Corgi Books London, 2005)
In Alagaesia, a fifteen-year-old boy of unknown lineage called Eragon finds a mysterious stone that weaves his life into an intricate tapestry of destiny, magic, and power, peopled with dragons, elves, and monsters